IDENTIFIKASI JENIS INFILL PATTERN PADA PROSES 3D PRINTING YANG MENGHASILKAN HASIL CETAK DENGAN KEKUATAN TEKAN DAN PANJANG FILAMEN YANG OPTIMAL - Samuel Eluzai Yedija Wijayanto; Rico Handoko; Jesslyne Chenia Noel; Timotius William Anggawirawan; The Jaya Suteja (Jurnal Rekayasa Mesin, 2022)
3D Printing technology becomes a potential solution to build various customized leg prosthetics. As a leg prosthetic must be able to hold a compressive force, it is important to find the compressive strength of the 3D printed part. The aim of this research is to find the infill pattern type which produces the 3D printed part with the highest compressive strength and the shortest filament length. This research uses the Fused Filament Fabrication method to print 24 parts made of Polylactic Acid using 12 different infill patterns with 50% density. All printed parts are designed to replicate the ASTM D695 specimen. After that, the compressive strength of each part is measured by using a Universal Testing Machine. And the filament length of each part is estimated by using slicer software. Based on the experiment result, the infill pattern with the highest compressive strength is the 3D Honeycomb type. However, this infill pattern requires the longest filament length compared to other infill patterns. In order to achieve a similar value of compressive strength with the minimum required material, the Cubic type is recommended to be implemented.